2011
DOI: 10.1080/14790718.2011.588332
|View full text |Cite
|
Sign up to set email alerts
|

Early requestive development in consecutive third language learning

Abstract: While research on early simultaneous bilingual acquisition is well-documented, studies on multiple language acquisition in early childhood are still needed. Existing studies have mainly focused on early simultaneous acquisition of three or more languages). Some attention has already been paid to early pragmatic differentiation and cross-linguistic influence. Nevertheless, the effects of the successive acquisition of two or more languages in early childhood are still underresearched. The main aim of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…In fact, only a few studies have adopted a multilingual perspective to explore pragmatic comprehension (Portolés, 2015;Safont-Jordà and Portolés, 2015) and production (Portolés and Safont-Jordà, 2013;Safont-Jordà, 2011. Research from a multilingual perspective has also provided evidence for the interaction between languages in multilinguals.…”
Section: Pragmatics In Multilingual Written Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, only a few studies have adopted a multilingual perspective to explore pragmatic comprehension (Portolés, 2015;Safont-Jordà and Portolés, 2015) and production (Portolés and Safont-Jordà, 2013;Safont-Jordà, 2011. Research from a multilingual perspective has also provided evidence for the interaction between languages in multilinguals.…”
Section: Pragmatics In Multilingual Written Productionmentioning
confidence: 99%
“…As far as we are aware, the only longitudinal studies taking a multilingual perspective are those by Safont-Jordà (2011, which were conducted outside the classroom.…”
Section: Pragmatics In Multilingual Written Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) metalinguistic awareness, (2) more learning mechanisms, and (3) a more extensive linguistic repertoire. Monolingual speakers differ from bilingual speakers in the learning process ( Thomas, 1988 ; Cenoz and Genesee, 1998 ; De Angelis, 2005 ; Safont-Jordà, 2011 ), as the latter already know another language, i.e., more than one linguistic inventory ( Nayak et al, 1990 ; Bialystok et al, 2004 ; Tremblay and Sabourin, 2012 ; Cenoz, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a positive effect of bilingualism on awareness and use of pragmatic strategies has been reported (Portolés, 2015). Studies have also revealed a dynamic relationship among languages in multilinguals; Multiple languages influence one another at the pragmatic level, both in elicited data taken from formal contexts of instruction (Martín-Laguna & Alcón-Soler, 2018) and in authentic data from multilingual families' interactions (Safont-Jordà, 2011.…”
Section: Pragmatics and The Multilingual Turnmentioning
confidence: 99%